The Increment of Titi Plant (Gmelina moluccana) at 10 Years in the Hatusua Region, Kairatu District - Absalom Dado Massolo; Febian F Tetelay; Hendrik S.E.S Aponno (Jurnal Sylva Scienteae, 2024)
ABSTRACT. The purpose of this study was to determine the height and diameter increment of Titi plant (Gmelina moluccana) 10 years after planting, as well as the environmental factors influencing them. The study method employed a descriptive approach with observational techniques in the field. Data collection involved direct observations in the example II Titi plot (Gmelina moluccana), covering an area of 1 hectare with a planting distance of 3x3. The total number of Titi plant taken in the sample plot was 75 trees. Data analysis utilized quantitative analysis with the mean annual increment, current annual increment, and multiple linear regression analysis methods. The observed environmental variables included soil pH, soil moisture, air temperature, air humidity, and rainfall. The results of the study indicated that the Current Annual Increment (CAI) of diameter in the tenth year was 1.7 (cm/tnm/year), and the Mean Annual Increment (MAI) of diameter was 2.40 (cm/tnm/year). The Current Annual Increment Increment (CAI) of height was 1.99 (m/tnm/year), and the Mean Annual Increment (MAI) of height was 1.62 (m/tnm/year). Factors influencing the growth of Titi plant (Gmelina moluccana) in the Hatusua Seed Source Demonstration Plot were soil pH and soil moisture.